PRODUCTION AND DISTRIBUTION FROM ISLAMIC ECONOMIC PERSPECTIVE - Adi, Asriadi Arifin (Journal of Sharia Economics, 2024)
In Islamic economics, production and distribution are the main pillars for achieving happiness, Islam bases production on the purpose of utilization, that production is a springboard for achieving value benefits and a more collective utilization goal that touches all groups. The presence of this paper is to examine the inherent (close relationship) of the concept of production and distribution based on an Islamic view. The results of this study will become a new discourse in Islamic economics literature as a contribution in the theoretical field for the perfection of the results of future studies. The type of research used is library research by referring to the written content of relevant research and then elaborating it with current phenomena. The conclusion states that Islam is a religion of rahmatan lil -' alamin which implies the distribution of goodness and benefit to every creature created by Allah SWT on earth, therefore this is a principle that is absorbed in Islamic economics so that it wards off all forms of production and distribution activities that are not in harmony with it. So that all human economic activities as caliphs must be verified based on Islamic normative values. Between the concepts of production and distribution, according to Islam, both are not a separate entity, but are a fragment. The main motive that must precede production is distribution, that someone who works has no other motive than himself and to ensure the fulfillment of the needs of others for the sake of realizing prosperity, economic justice and a balanced standard of living among all elements of society .